2009
DOI: 10.1158/1078-0432.ccr-08-1883
|View full text |Cite
|
Sign up to set email alerts
|

Cells with Characteristics of Cancer Stem/Progenitor Cells Express the CD133 Antigen in Human Endometrial Tumors

Abstract: Purpose: Cancer stem cells represent an attractive therapeutic target for tumor eradication. The present study aimed to determine whether CD133 expression may identify cells with characteristics of cancer stem/progenitor cells in human endometrial tumors. Experimental Design: We analyzed 113 tumor samples for CD133/1expression by flow cytometry, immunohistochemistry, and semiquantitative reverse transcription^PCR. CD133 + cells were isolated and used to assess phenotypic characteristics, self-renewal capacity,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
1
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(166 citation statements)
references
References 62 publications
7
150
1
8
Order By: Relevance
“…However, the process is evidently complex, and inflammation may contribute to tumour initiation in certain cases, by working in conjunction with other mechanisms (Fortuny et al 2009). Cancer growth may therefore be initiated by genetic mutations, possibly in endometrial stem cells (Rutella et al 2009), causing uncontrolled proliferation and subsequent cellular changes. These genetic changes may be a result of increased proliferation driven by an increased oestrogen to progesterone ratio in endometrial adenocarcinoma, in agreement with the unopposed oestrogen hypothesis (Jazaeri et al 2001).…”
Section: Conclusion: Endometrial Adenocarcinoma and Inflammationmentioning
confidence: 99%
“…However, the process is evidently complex, and inflammation may contribute to tumour initiation in certain cases, by working in conjunction with other mechanisms (Fortuny et al 2009). Cancer growth may therefore be initiated by genetic mutations, possibly in endometrial stem cells (Rutella et al 2009), causing uncontrolled proliferation and subsequent cellular changes. These genetic changes may be a result of increased proliferation driven by an increased oestrogen to progesterone ratio in endometrial adenocarcinoma, in agreement with the unopposed oestrogen hypothesis (Jazaeri et al 2001).…”
Section: Conclusion: Endometrial Adenocarcinoma and Inflammationmentioning
confidence: 99%
“…In addition, we demonstrated that CD133 + CSCs isolated from endometrial cancer express the tumour-associated antigen mucin-1 (MUC1). MUC1 make these cells potentially susceptible to immune system attack and contributes to maintaining resistance to cisplatin and paclitaxel (29). Again, CD133 expression was found to be the only independent risk factor in 1,366 patients affected by ovarian cancer with central nervous system metastasis (30).…”
Section: Discussionmentioning
confidence: 97%
“…The high expression of CD133 in ccRCC with favorable clinicopathological characteristics was an unexpected result, as CD133 has been applied as a putative CSC marker in numerous malignant tumors, and its high expression has been considered a poor prognostic factor. CD133 is currently applied as a cell-surface marker to isolate CSCs in malignant tumors of the colon, brain, lung, prostate, pancreas, liver, stomach and uterus (11,(25)(26)(27). A CD133…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer, high levels of CD133 expression were associated with a shorter relapse-free interval and poor overall survival (31). Furthermore, CSCs appear to be highly resistant to chemoradiation therapy (26,(32)(33)(34). In an atypical teratoid/rhabdoid tumor of the brain, high levels of CD133 + cells were positively correlated with radioresistance (35).…”
Section: Discussionmentioning
confidence: 99%